Flores and Miss Paula : a novel - Rivero, Melissa (Ecco, an imprint of HarperCollins Publishers, 2023)
"Thirtysomething Flores and her mother, Paula, still live in the same Brooklyn apartment, but that may be the only thing they have in common. It's been nearly three years since they lost beloved husband and father Martín, who had always been the bridge between them. One day, cleaning beneath his urn, Flores discovers a note written in her mother's handwriting: Perdóname si te falle. Recuerda que siempre te quise. ("Forgive me if I failed you. Remember that I always loved you.") But what would Paula need forgiveness for? Now newfound doubts and old memories come flooding in, complicating each woman's efforts to carve out a good life for herself--and to support the other in the same."--Publisher's site.